Assessing Financial Literacy Among Members of Agricultural Cooperatives in Cateel, Davao Oriental: A Quantitative Approach - Antenorio, Dem Francis S.; Lintogonan, Cecille D.; Mendez, Mary Lovely Suzzeth P. (Future Science / FSH-PH Publications, 2025)
This study explored the level of financial literacy among 68 cooperative members in Cateel, Davao Oriental. It aimed to examine the respondents' profiles in terms of age, gender, educational background, and income level, and to assess financial literacy across four dimensions: financial knowledge, behavior, awareness, and attitudes. Using weighted mean and ANOVA for data analysis, the study identified significant differences in financial literacy based on demographic factors. Results showed that most respondents were young and had varied educational backgrounds. Financial behavior significantly differed by age (p < 0.05), while educational attainment had a significant impact on financial knowledge, behavior, and attitude (p < 0.05), and a near-significant effect on overall financial literacy. Gender differences were significant in financial behavior, attitude, and overall financial literacy. However, no significant differences were found based on income level or prior financial literacy training. These findings underscore the importance of designing targeted financial education interventions that address age-, gender-, and education-related disparities to improve financial literacy among cooperative members.